2012
DOI: 10.1097/prs.0b013e318262f3a9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Columellar Strut Graft on Nasal Tip Position in Primary Rhinoplasty

Abstract: Use of the columellar strut cartilage graft does not necessarily imply an increase in tip projection, but rather serves as a means of unifying the nasal tip and helping to control final tip position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 0 publications
5
67
0
1
Order By: Relevance
“…1 However columellar struts have some limitations, they are subject to both resorption and displacement, 2 and as they are not attached to the caudal septum post operative tip drooping may occur. 6 In their study to know the effect of columellar strut on final tip position Rhorich et al 7 analyzed the tip projection, columellar-labial angle and nasofrontal angle in 100 rhinoplasty patients, the columellar-labial angle was increased in only 46% and unchanged in 20%, while it decreased in 34%. They also found that tip projection decreased in 65%, increased in 27%, and was unchanged in 8% of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…1 However columellar struts have some limitations, they are subject to both resorption and displacement, 2 and as they are not attached to the caudal septum post operative tip drooping may occur. 6 In their study to know the effect of columellar strut on final tip position Rhorich et al 7 analyzed the tip projection, columellar-labial angle and nasofrontal angle in 100 rhinoplasty patients, the columellar-labial angle was increased in only 46% and unchanged in 20%, while it decreased in 34%. They also found that tip projection decreased in 65%, increased in 27%, and was unchanged in 8% of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rhorich study including 100 rhinoplasty patients with retracted columella, although 67 % of the patients could reach NLA increasing, still 23 % finally experienced statistically significant NLA reduction [13].…”
Section: Discussionmentioning
confidence: 99%
“…The columellar strut has been a mainstay to maintain tip support in rhinoplasty surgery. [4][5][6][7] Some have suggested that columellar struts or tip reconstruction may not be necessary if tip support mechanisms are not disrupted. 19 We have found that this is true only in very rare cases.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] While many find this technique quite reliable, pitfalls include clicking of the strut on the nasal spine and poor control of (or excess) columellar show. [6][7][8] Furthermore, this technique requires autologous cartilage harvest, usually from the septum, although rib or ear may be used. While many of these challenges can be overcome with proper technique and are surgeon-and technique-dependent, we find the primary drawback of columellar strut grafting is its reliability to precisely set tip projection and rotation.…”
mentioning
confidence: 99%